EVALUATION OF ANTIMICROBIAL RESISTANCE PATTERNS IN COMMUNITY PHARMACIES: IMPLICATIONS FOR ANTIBIOTIC STEWARDSHIP - Majed Ahmed Alwadine, Abdullah Abdulqader Alasami, Mohammed Mukhlid Alharbi, ‏‏Sultan Gublan Hussain Alsohimi, Anwar Ali Hakami, Osamah Fahad Almalki, Odai Gawad Alakili, Mohammed Ibrahim Mohammed Alrajhi, ,; Sultanah Hamoud Alshammari, Ibrahim Ali Yahya Tumayhi, Hussain Ali Ahmed Marwee, Hakem Bijad Mutiq Alrakhimi, Ahmed Nahari Madkhali, Yousef Mousa Essa Ayashi, Mohammed Ali Alhazmi, Roaa Ahmad Shbaily, (Chelonian Research Foundation, 2022)
The discussion highlights the pivotal role of community pharmacists in addressing antimicrobial resistance (AMR) through responsible antibiotic dispensing practices and patient education. Despite challenges such as improper antibiotic use and patient demand for antibiotics without prescriptions, recent pharmacist-led interventions have shown promise in improving antibiotic prescribing practices. Collaboration among healthcare professionals, policymakers, and the public is crucial in addressing the multifaceted factors contributing to AMR. Public awareness campaigns and efforts to improve access to healthcare services are essential in fostering a culture of responsible antibiotic use. Community pharmacists, equipped with their expertise, are well-positioned to play a central role in combating AMR. Through ongoing education and training, pharmacists can enhance their knowledge and skills in antimicrobial stewardship, ultimately contributing to the mitigation of AMR and safeguarding public health.